Integrated computational tools for virtual and physical automatic construction - Alves, N. M. (2006)
Recent advances in computer tools have improved the ability to store, navigate and display large and complex three-dimensional (3D) models, a step forward in architectural and urban planning. The generation of photo-realistic models is a time-consuming task that requires significant human input, despite current developments in photogrammetry and 3D scanning technology. Though computer vision techniques operate automatically, they do not produce usable models, frequently being weak with respect to occlusion and changes in illumination, on top of operating with small sets of images. To solve these limitations, this research work uses a new biologically based system, called BioCAD, which mimics the human vision process. This novel system is specifically designed for the rapid and accurate generation of 3D computer models from existing large objects, like buildings, allowing a direct link to rapid prototyping systems. AWorld Heritage building was chosen as a case study to validate BioCAD.